2011
DOI: 10.5194/cp-7-815-2011
|View full text |Cite
|
Sign up to set email alerts
|

Holocene evolution of summer winds and marine productivity in the tropical Indian Ocean in response to insolation forcing: data-model comparison

Abstract: Abstract. The relative abundance of Globigerinoides bulloides was used to infer Holocene paleo-productivity changes on the Oman margin and at the southern tip of India. Today, the primary productivity at both sites reaches its maximum during the summer season, when monsoon winds result in local Eckman pumping, which brings more nutrients to the surface. On a millennium time-scale, however, the % G. bulloides records indicate an opposite evolution of paleo-productivity at these sites through the Holocene. The O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
57
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 64 publications
(89 reference statements)
9
57
0
Order By: Relevance
“…Results show that the early Holocene humid period corresponds to a decrease in coastal upwelling. This decrease in upwelling intensity off western Africa is out of phase, therefore, with the early Holocene increase in western Arabian sea upwelling [e.g., Bassinot et al, 2011]. Although no data is available to estimate and correct past changes in age reservoir at ODP 658, we expect that 14 C-derived chronologies of sites 74KL and ODP 658 may be off by several hundred years over specific intervals due to changes in upwelling intensity.…”
Section: Marine Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Results show that the early Holocene humid period corresponds to a decrease in coastal upwelling. This decrease in upwelling intensity off western Africa is out of phase, therefore, with the early Holocene increase in western Arabian sea upwelling [e.g., Bassinot et al, 2011]. Although no data is available to estimate and correct past changes in age reservoir at ODP 658, we expect that 14 C-derived chronologies of sites 74KL and ODP 658 may be off by several hundred years over specific intervals due to changes in upwelling intensity.…”
Section: Marine Datamentioning
confidence: 99%
“…Several studies combining proxy data and climate model simulations have shown that changes in insolation controlled by the slow variation of the Earth orbital parameters (mainly precession), have been the major driver of Holocene changes in atmospheric circulation and in the hydrological budget, which are ultimately linked to the afro-asian monsoon system [e.g. COHMAP, 1988;Prell and Kutzbach, 1987;Joussaume et al, 1999;Liu et al, 2003;Marzin and Braconnot, 2009 a,b;Bassinot et al, 2011;Lézine et al, 2011a]. During the first half of the Holocene, orbital configuration resulted in enhanced seasonality in northern tropical areas compared to the late Holocene.…”
Section: Introductionmentioning
confidence: 99%
“…At ODP site 1082, core‐top planktonic foraminifera assemblages are dominated by the subpolar species G. bulloides and Neogloboquadrina pachyderma (right coiling) [ Giraudeau , ]. High abundance of G. bulloides at low latitudes is globally associated with upwelling environments [ Lombard et al ., ], one ecological characteristic used to reconstruct primary productivity of tropical upwelling systems by means of G. bulloides countings [ Gupta et al ., ; Bassinot et al ., ]. We hence anticipate the Mg/Ca‐derived SST reconstruction based on that species to be reflective of seasons with SST below the mean‐annual SST, i.e., when upwelling intensifies.…”
Section: Theoretical Background On Sst Proxies Specificitiesmentioning
confidence: 99%
“…High abundance of G. bulloides at low latitudes is globally associated with upwelling environments bulloides tests for foraminifera dated at 2.23, 2.74, and 3.37, i.e., for times when high, intermediate and low opal MAR were recorded, respectively. , one ecological characteristic used to reconstruct primary productivity of tropical upwelling systems by means of G. bulloides countings [Gupta et al, 2003;Bassinot et al, 2011]. We hence anticipate the Mg/Caderived SST reconstruction based on that species to be reflective of seasons with SST below the mean-annual SST, i.e., when upwelling intensifies.…”
Section: Theoretical Background On Sst Proxies Specificitiesmentioning
confidence: 99%
“…The pollen sequences from the respective sites have also offered insights into the changing floristic patterns and the coeval climatic episodes. Besides pollen, other proxies like foraminifera (Nagender Nath et al 2012;Bassinot et al 2011;Banakar et al 2010;Khare et al 2008), foraminiferal isotopic and elemental data (Saraswat et al 2013), rock magnetic properties (Anil Kumar et al 2005;Thamban et al 2007), oxygen isotopes (Prabhu et al 2004), nitrogen isotopes (d 15 N; Agnihotri et al 2008), geochemical parameters (Chauhan et al 2010a), biomarkers (Kurian et al 2009), and clay mineral data (Chauhan et al 2010a) of marine sediments have also been employed in reconstructing the palaeoclimate of the region. However, most of these do not provide much information on the important climatic events of the Holocene.…”
Section: Introductionmentioning
confidence: 98%